Most Significant Change in conflict settings: staff development through monitoring and evaluation. Issue 1 (2nd January 2016) - Kraft, Kathryn; Prytherch, Hannah
ABSTRACT: Capoeira4Refugees is an NGO that uses the Afro-Brazilian art form of Capoeira to promote psychosocial well-being in children affected by conflict and occupation. Capoeira4Refugees introduced the Most Significant Change (MSC) methodology to monitor and evaluate project implementation and impact across two locations in the Middle East. Analysis of interviews conducted with five field staff revealed that in line with, and building on, previous research, MSC became an empowering tool that led to staff development. The potential for MSC to build staff reflexivity, independence, and leadership has implications for other organisations working in conflict areas, particularly in situations of remote management.